FEM Updating for Offshore Jacket Structures Using Measured Incomplete Modal Data - Farhad Hosseinlou; Alireza Mojtahedi (International Journal of Maritime Technology, 2016)
Marine industry requires continued development of new technologies in order to produce oil. An essential requirement in design is to be able to compare experimental data from prototype structures with predicted information from a corresponding analytical finite element model. In this study, structural model updating may be defined as the fit of an existing analytical model in the light of measured vibration test. After fitting, the updated model is expected to represent the dynamic behavior of the jacket structure more precisely. In this way, current article presents a direct based updating study of a reduced scale four-story spatial frame jacket structure fabricated and tested at mechanical system and signal processing laboratory. Also, an efficient model updating process is presented with limited modal data, which uses modal data in order to improve the correlation between the experimental and analytical models.